New Patient Orientation “KANAK”(Recognizing Pediatric Room) to Prevent Child Hospitalization - Essy Sonontiko; Dodi Wijaya; Diana Rochma; Yuliah Ernawati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Sick children experience crisis conditions for a change of environment when they have to be hospitalized. Besides that, children must be separated from their closest people and cannot do any activities such as playing. This condition is called hospitalization. New patient orientation is an introduction provided by nurses to patients and families about the services while the children are undergoing treatment in order to be able to adapt immediately, one of which is to prevent hospitalization. Objective: Optimizing the implementation of new patient orientation “KANAK” (Recognizing Pediatric Room) through leaflet and barcode features. Methods: This study used a descriptive research design with a pilot study approach. The sample of this study was families of new patients in the pediatric room of Blambangan Hospital. The instruments used were KANAK guidelines, leaflets and barcode features. Results: The results of observations of the implementation of KANAK in the pediatric room to families using leaflets and barcode features carried out by the team leader and shift supervisor for 15 patients were categorized as good. Conclusion: The implementation of new patient orientation through a pilot study approach applying SWOT Analysis and implementing the PDCA concept (Plan, Do, Check and Action) during the evaluation, decreased child hospitalization.